LncRNA OIP5-AS1 Regulates the Warburg Effect Through miR-124-5p/IDH2/HIF-1α Pathway in Cervical Cancer - Li, Li; Ma, Yan; Maerkeya, Kamalibaike; Reyanguly, Davuti; Han, Lili (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia reprogrammed glucose metabolism affects the Warburg effect of tumor cells, but the mechanism is still unclear. Long-chain non-coding RNA has been found by many studies to be involved in the Warburg effect of tumor cells under hypoxic condition. Herein, we find that lncRNA OIP5-AS1 is up-regulated in cervical cancer tissues and predicts poor 5-years overall survival in cervical cancer patients, and it promotes cell proliferation of cervical cancer cells in vitro and in vivo. Moreover, OIP5-AS1 is a hypoxia-responsive lncRNA and is essential for hypoxia-enhanced glycolysis which is IDH2 or HIF-1α dependent. In cervical cancer cells, OIP5-AS1 promotes IDH2 expression by inhibiting miR-124-5p, and IDH2 promotes the Warburg effect of cervical under hypoxic condition through regulating HIF-1α expression. In conclusion, hypoxia induced OIP5-AS1 promotes the Warburg effect through miR-124-5p / IDH2 / HIF-1α pathway in cervical cancer.